2003
DOI: 10.2527/2003.81102515x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chromium propionate on growth, carcass traits, pork quality, and plasma metabolites in growing-finishing pigs1,2

Abstract: Two experiments were conducted to determine the effects of dietary Cr, as Cr propionate, on growth, carcass traits, pork quality, and plasma metabolites in growing-finishing swine. Ninety-six crossbred gilts (Exp. 1; initial and final BW of 28 [SEM = 0.41] and 109 [SEM = 2.11] kg) or 144 PIC Cambrough 22 barrows (Exp. 2; initial and final BW of 26 [SEM = 0.39] and 111 [SEM = 2.52] kg) were allotted to six or four dietary treatments, respectively, with six replications and four (Exp. 1) or six (Exp. 2) pigs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 21 publications
5
23
1
3
Order By: Relevance
“…However, reports from Clancy et al(1994) and Campbell et al(1999) did not support an effect of supplemental Cr on altering body composition. The dosages in studies on rats (Hasten et al, 1993), pigs (Shelton et al, 2003) and steers (Pollard et al, 2002), which have observable changes in body composition due to Cr supplementation ranged from 25 to 1 000 ppb. In the present study, LBM was increased by the addition of 300 and 450 ppb Cr as CrNano and %BF was decreased by the addition of 150, 300, 450, and 600 ppb Cr as CrNano.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reports from Clancy et al(1994) and Campbell et al(1999) did not support an effect of supplemental Cr on altering body composition. The dosages in studies on rats (Hasten et al, 1993), pigs (Shelton et al, 2003) and steers (Pollard et al, 2002), which have observable changes in body composition due to Cr supplementation ranged from 25 to 1 000 ppb. In the present study, LBM was increased by the addition of 300 and 450 ppb Cr as CrNano and %BF was decreased by the addition of 150, 300, 450, and 600 ppb Cr as CrNano.…”
Section: Discussionmentioning
confidence: 99%
“…In swine, Page et al(1993) found that changes of body composition (increase in longissimus muscle area and percentage of muscling, and decrease in the 10th rib fat) took place at Cr levels of 100, 200, 400, and 800 µg Cr/kg feed (also expressed as parts per billion, ppb), but growth rate was decreased at the higher levels of 400 and 800 ppb. The dosages in animal studies which have observed increases in lean body mass of rats (Hasten et al, 1993) and pigs (Shelton et al, 2003) and decreases in body fat of pigs (Lindemann et al, 1993) and steers (Pollard et al, 2002) due to Cr supplementation ranged from 25 to 1 000 ppb. Furthermore, Lindemann et al(1993) found linear increases in lean body mass with linear decreases in body fat in swine for chromium picolinate (CrPic) additions of 100, 200, and 1 000 ppb Cr.…”
Section: Introductionmentioning
confidence: 99%
“…Chromium sources used in animal experiments were chromium picolinate (CrPic), chromium nicotinate, chromium chloride and less Cr propionate, but some authors consider that the organic source of Cr is over ten times more bioavailable than inorganic sources (Shelton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Most published research refers to the longissimus muscle area and total carcass lean (Shelton et al, 2003), drip loss in chops (Wang & Xu, 2004), loin pH, drip and purge loss (Matthews et al, 2005), backfat and the iodine value of belly (Jackson et al, 2009), carcass lean ratio and carcass fat ratio (Wang et al, 2014), and meat colour (Li et al, 2013). The concentrations of protein and fat are critical attributes of carcass quality (Monziols et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While chromium chloride has been successful in improving growth performance of poultry (Steele and Rosebrough 1979;Uyanik et al 2002) or protein-deficient rats (Mertz and Roginski 1969), effects in pigs (Page et al 1993;Mooney and Cromwell 1995;Shelton et al 2003) and ruminants (Kegley et al 1997a;Kegley et al 2000) have been more equivocal. In part, this may reflect variability in absorption of chromium, since the absorption and utilisation of chromium may depend on incorporation into organic molecules (Evans and Johnson 1980;Kegley et al 1997b).…”
Section: Betainementioning
confidence: 99%